Sensing and imaging based on novel laser techniques - Tan, Jia Min (2017)
After the remarkable discovery of light transmission through the subwavelength hole arrays, there has been a growing interest in nano-structured metallic systems for their optical properties due to their rich underlying physics purpose and its contribution to novel optical applications. Therefore, in this Final Year Project report, the author will demonstrate how a nano-slit surrounded by metallic heterostructure that is being constructed with metals such as Aluminium and Silver can be used to attain directional beaming of light. Furthermore, the author will also show that the formation of electromagnetic surface resonances is the cause of beaming and the beam direction can be controlled by fine tuning the geometric properties of the structure. The author will also extend the results obtained from the metallic heterostructure to further improve the beaming effect. Lastly, all the simulations were done using Lumerical Finite Difference Time Domain (FDTD) software which is a three dimensional full wave solver that employs finite integration method.